Collagen type I induces EGFR‐TKI resistance in EGFR‐mutated cancer cells by mTOR activation through Akt‐independent pathway. Issue 6 (6th June 2018) - Yamazaki, Shota; Higuchi, Youichi; Ishibashi, Masayuki; Hashimoto, Hiroko; Yasunaga, Masahiro; Matsumura, Yasuhiro; Tsuchihara, Katsuya; Tsuboi, Masahiro; Goto, Koichi; Ochiai, Atsushi; Ishii, Genichiro
Abstract : Primary resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) is a serious problem in lung adenocarcinoma patients harboring EGFR mutations. The aim of this study was to examine whether and how collagen type I (Col I), the most abundantly deposited matrix in tumor stroma, affects EGFR‐TKI sensitivity in EGFR‐mutant cells. We evaluated the EGFR‐TKI sensitivity of EGFR ‐mutated cancer cells cultured with Col I. Changes in the activation of downstream signaling molecules of EGFR were analyzed. We also examined the association between the Col I expression in tumor stroma in surgical specimens and EGFR‐TKI response of postoperative recurrence patients with EGFR mutations. Compared to cancer cells without Col I, the survival rate of cancer cells cultured with Col I was significantly higher after EGFR‐TKI treatment. In cancer cells cultured with and without Col I, EGFR‐TKI suppressed the levels of phosphorylated (p‐)EGFR, p‐ERK1/2, and p‐Akt. When compared to cancer cells without Col I, expression of p‐P70S6K, a hallmark of mTOR activation, was dramatically upregulated in cancer cells with Col I. This activation was maintained even after EGFR‐TKI treatment. Simultaneous treatment with EGFR‐TKI and mTOR inhibitor abrogated Col I‐induced resistance to EGFR‐TKI. Patients with Col I‐rich stroma had a significantly shorter progression‐free survival time after EGFR‐TKI therapy (238 days vs 404 days; P  < .05). Collagen type I induces mTOR activation through an Akt‐independent pathway, which results in EGFR‐TKI resistance. Combination therapy using EGFR‐TKI and mTOR inhibitor could be a possible strategy to combat this resistance. Abstract : Collagen type I induces EGFR‐TKI resistance in EGFR‐mutated cancer cells via mTOR activation through Akt‐independent pathway.This study demonstrates a novel strategy for increasing the therapeutic effect of EGFR‐TKI.